Grey Wolf Optimizer-Based Predictive Torque Control for Electric Buses Applications - Ali Djerioui; Azeddine Houari; Mohamed Machmoum; Malek Ghanes (Energies, 2020)
This paper proposes an improved Predictive Torque Control (PTC) of a PMSM based on the Grey Wolf Optimizer (GWO) for smooth torque operation in Electric Bus applications (EBs). The embedded GWO is used to resolve the torque tracking tasks with minimal oscillations in running at the low speed of PMSM drives. The new PTC algorithm can successfully ensure the smooth time evolution of the torque and the speed. The design methodology is detailed and the provided experimental results show that the proposed PTC-GWO can be implemented in real-time on embedded hardware, offering high effectiveness in both steady and transient states of the PMSM drives, even at low-speed range.